2016
DOI: 10.1093/infdis/jiw280
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Syndromic Surveillance of Influenza in Europe

Abstract: The growth of digital communication technologies for public health is offering an unconventional means to engage the general public in monitoring community health. Here we present Influenzanet, a participatory system for the syndromic surveillance of influenza-like illness (ILI) in Europe. Through standardized online surveys, the system collects detailed profile information and self-reported symptoms volunteered by participants resident in the Influenzanet countries. Established in 2009, it now includes 10 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 26 publications
5
103
0
Order By: Relevance
“…One found that public transport used within 5 days of symptoms onset was associated with an increased risk of consulting for acute respiratory infection [31]. Previous Influenzanet works did not find an association between public transport and influenza [16, 21, 32], likely because of lack of statistical power due to the consideration of one season only [16, 21] or due to methodological differences based on the public transport covariate definition [32]. In this last article, the public transport covariate was defined using three categories (bicycle/foot, car and public transport), whereas here we opted for two categories (private vs. public transports) in order to better observe any impact of public transports with respect to other modes of daily locomotion, where individuals do not have close contacts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One found that public transport used within 5 days of symptoms onset was associated with an increased risk of consulting for acute respiratory infection [31]. Previous Influenzanet works did not find an association between public transport and influenza [16, 21, 32], likely because of lack of statistical power due to the consideration of one season only [16, 21] or due to methodological differences based on the public transport covariate definition [32]. In this last article, the public transport covariate was defined using three categories (bicycle/foot, car and public transport), whereas here we opted for two categories (private vs. public transports) in order to better observe any impact of public transports with respect to other modes of daily locomotion, where individuals do not have close contacts.…”
Section: Discussionmentioning
confidence: 99%
“…This profile survey can be updated throughout the season, and covers socio-demographic (gender, age, household composition, occupation, place of residency); lifestyle (having pets, daily contacts, daily transportation means, smoking habit); and health-related characteristics (height and weight to estimate the body mass index (BMI), chronic treatments for at least one comorbidity including asthma, diabetes, immunosuppression, heart, kidney or pulmonary diseases, influenza vaccination status for the current and past seasons, respiratory allergies) [17, 18]. After the profile completion, symptoms data are collected on a weekly basis [1416]. If symptoms are reported (from a list of 19 symptoms), further questions are asked to detail them and the participant behavior [19].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations